2020
DOI: 10.1101/2020.07.30.228999
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dystrophic microglia are a disease associated microglia morphology in the human brain

Abstract: Microglia activation—typically described in terms of hypertrophic appearance—is a well-established feature of aging. Recent studies have suggested that microglia dystrophy, not activation, may increase the propagation of progressive neurodegenerative diseases such as Alzheimer’s disease (AD). Yet, a clear understanding of cause and consequences of dystrophic microglia is lacking. Although frequently observed in diseased brains, the appearance of dystrophic microglia in the hippocampus of individuals free of co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Chronological aging is associated with a significant increase in the total numbers of both hypertrophic as well as dystrophic microglia. A recent study showed that dystrophy are the disease associated microglia morphology 21 . In the present study we see evidence for increased microglial cells in the COVID-19 eyes and several of these appear to show the characteristic of microglial dystrophy and hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronological aging is associated with a significant increase in the total numbers of both hypertrophic as well as dystrophic microglia. A recent study showed that dystrophy are the disease associated microglia morphology 21 . In the present study we see evidence for increased microglial cells in the COVID-19 eyes and several of these appear to show the characteristic of microglial dystrophy and hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of aging, an increasing proportion of microglial cells display abnormal morphological features such as shortened, gnarled, beaded, or fragmented cytoplasmic processes, and loss of fine ramifications and formation of spheroidal swellings; these changes are designated collectively as microglial dystrophy 20 . These changes are determined to be different than what occurs during microglial activation which is defined as hypertrophic microglia [20][21][22][23] . In all the eyes examined, there was evidence for both hypertrophic and dystrophic microglia, though there was evidence of microglial dystrophy in 2.…”
Section: Gliosis and Increased Infiltration Of Microglial Cells In Thmentioning
confidence: 99%
“…We next sought to explore whether our DS microglial mouse chimera could recapitulate the dystrophic microglia pathology found in AD and DSAD human brain tissues (Braak and Del Tredici, 2015; Jimenez et al, 2008; Martini et al, 2020; Meyer-Luehmann and Prinz, 2015; Sanchez-Mejias et al, 2016; Shahidehpour et al, 2020; Streit et al, 2009; Xue and Streit, 2011). Previous in vitro studies demonstrated that soluble p-tau in human AD brain tissue extracts induced microglial degeneration (Sanchez-Mejias et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Although the amyloid cascade/neuroinflammation theory of AD has been widely accepted, several caveats have arisen. The microglial responses observed in the hippocampus of APPbased mouse models differ from those observed in AD and DSAD patients (Braak and Del Tredici, 2015;Jimenez et al, 2008;Meyer-Luehmann and Prinz, 2015;Sanchez-Mejias et al, 2016;Shahidehpour et al, 2020;Streit et al, 2009;Xue and Streit, 2011). More importantly, non-steroidal anti-inflammatory drugs have demonstrated no clear ability to delay onset or reverse cognitive dysfunction in AD patients (Arvanitakis et al, 2008;Green et al, 2009;Group et al, 2007;Group et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Microglial cells changed with an increase in ramified morphology, and most migrated to the retinal vessels in the GCL and nerve fiber layer. Recent studies have shown that dystrophy is a disease associated with microglial morphology [ 32 ] and brain alterations in COVID-19 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%